IMPACT OF CONSUMER PERCEPTION ON PURCHASE INTENTION OF LUXURY PRODUCTS - Balakumaran, S.; Ramkumar, M. (International Journal of Research -GRANTHAALAYAH, 2021)
Though the current era has seen a huge extent of recession, due to the Covid 19 issue. But, the consumption of luxury products is seen to be remaining unchanged, even after the recession period. The concept of luxury can be seen in every place. It is the term which is commonly used by the individuals in their daily life. Luxury is the dream of every person for leading an exclusive lifestyle. It is the main element in the field of marketing management and also is a tagline in the campaigns of advertising and commercials. The study is done to examine the effect of consumer perception on the purchase intention of the luxury products. The respondents of the study are the consumers of luxury products residing at Chennai and they are selected through simple random sampling. The collection of data needed for the study is carried out using a questionnaire and the analysis is done by executing regression. The results of analysis show that the purchase intention was highly influenced by the consumer perception.